Response to [ 177 Lu]Lu-PSMA radioligand therapy in metastatic castration-resistant prostate cancer patients presenting with only lymph node metastases - Zisser, Lucia; Yu, Josef; Oszwald, André; Wollenweber, Tim; Kretschmer-Chott, Elisabeth; Grubmüller, Bernhard; Kramer, Gero; Shariat, Shahrokh F; Mitterhauser, Markus; Vraka, Chrysoula; Hacker, Marcus; Haug, Alexander R; et al. (Nuclear medicine communications, 2022)
OBJECTIVE: [ 177 Lu]Lu-PSMA radioligand therapy (PSMA-RLT) is a promising therapy for patients with metastatic castration-resistant prostate cancer (mCRPC) and offers a survival benefit particularly to patients with only lymph node metastases. We therefore sought to evaluate the clinical outcome of this therapy in such a cohort. METHODS: Of all prostate cancer patients admitted to our department between September 2015 and March 2019 to receive 1-4 courses of PSMA-RLT (each course consisted of three cycles of highly standardized PSMA-RLT every 4 weeks), only 10 consecutive men were found to have nodal metastases only and were analyzed retrospectively. RESULTS: Nine out of 10 patients responded to their first PSMA-RLT course with a mean prostate-specific antigen (PSA) decline of 71.8 ± 25.2%, seven of them demonstrated a PSA decline of ≥50%. Collectively, seven of eight patients responded to further PSMA-RLT courses with a total PSA reduction of 59.8 ± 30.0%, five of which showed a PSA reduction of ≥50%. One patient experienced complete remission. Median progression-free survival was 85 weeks (range 14-255 weeks) and median overall survival was not reached during the median observation time of 209 weeks (30-298 weeks). Univariate Cox-regression identified initial PSA decline as the only predictive parameter for progression-free survival ( P = 0.047). CONCLUSION: mCRPC patients with only lymph node metastases showed favorable survival and excellent response to PSMA-RLT, leading to transient partial remission of the disease in most of them.
Keywords: radionuklidy; Male; retrospektivní studie; Lutetium; Dipeptides; mužské pohlaví; Prostatic Neoplasms, Castration-Resistant; nádory prostaty rezistentní na kastraci; Lymphatic Metastasis; prostatický specifický antigen; lidé; Heterocyclic Compounds, 1-Ring; Humans; Radioisotopes; dipeptidy; lymfatické metastázy; Retrospective Studies; lutecium; Prostate-Specific Antigen; heterocyklické sloučeniny monocyklické